Somatic mutation profiles of clear cell endometrial tumors revealed by whole exome and targeted gene sequencing - Le Gallo, Matthieu (Cancer, 2017)
BACKGROUND: The molecular pathogenesis of clear cell endometrial cancer (CCEC), a tumor type with a relatively unfavorable prognosis, is not well defined. We searched exome-wide for novel somatically mutated genes in CCECs, and assessed the mutational spectrum of known and candidate driver genes in a large cohort of cases. METHODS: We whole exome sequenced paired tumor-normal DNAs from 16 CCECs (12 CCECs and the CCEC components of four mixed histology tumors). Twenty-two genes-of-interest were Sanger sequenced from another 47 CCECs. Microsatellite instability and stability (MSI and MSS) were determined by genotyping five mononucleotide repeats. RESULTS: Two tumor exomes had relatively high mutational loads and MSI. The other 14 tumor exomes were MSS and had 236 validated nonsynonymous or splice junction somatic mutations among 222 protein-encoding genes. Among the 63 CCECs in this study, we identified frequent somatic mutations in TP53 (39.7%), PIK3CA (23.8%), PIK3R1 (15.9%), ARID1A (15.9%), PPP2R1A (15.9%), SPOP (14.3%), and TAF1 (9.5%), as well as MSI (11.3%). Five of eight mutations in TAF1, a gene with no known role in CCEC, localized to the putative histone acetyltransferase domain and included two recurrently mutated residues. Based on patterns of MSI and mutations in seven genes, subsets of CCECs molecularly resembled serous ECs (SECs) or endometrioid ECs (EECs). CONCLUSIONS: Our findings demonstrate molecular similarities between CCECs and SECs and EECs, and implicate TAF1 as a novel candidate CCEC driver gene.